2007
DOI: 10.1590/s0102-67202007000200006
|View full text |Cite
|
Sign up to set email alerts
|

Morbimortalidade da colecistectomia em pacientes idosos, operados pelas técnicas laparotômica, minilaparotômica e videolaparoscópica

Abstract: InTRODUÇÃOA colecistolitíase é uma das doenças mais freqüentes do aparelho digestivo, acometendo 20% da população adulta . Desde sua primeira descrição em 1882, por Langenbruch, a colecistectomia se mantém como o tratamento de escolha para a colecistolitíase . Desde essa época os cirurgiões tentam diminuir a morbidade, mortalidade e tempo de internação que é muito variável na literatura.A colecistectomia por minilaparotomia, divulgada por Goco e Chambers em 1982 3 e a colecistectomia videolaparoscópica, por Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
2
3
0
1
Order By: Relevance
“…We believe that this divergence is due to under-reporting of minor complications. The conversion rate to open surgery in our series was 2.9%, compared with 2.5 to 14% in LC other series studying elective for symptomatic cholelithiasis in the elderly 4,[17][18][19][20][21][22][23][24][25][26] , being similar to the conversion rate in young patients 4,27,28 , unlike Qasaimeh et al 29 , who reported higher conversion rates in the elderly.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We believe that this divergence is due to under-reporting of minor complications. The conversion rate to open surgery in our series was 2.9%, compared with 2.5 to 14% in LC other series studying elective for symptomatic cholelithiasis in the elderly 4,[17][18][19][20][21][22][23][24][25][26] , being similar to the conversion rate in young patients 4,27,28 , unlike Qasaimeh et al 29 , who reported higher conversion rates in the elderly.…”
Section: Discussion Discussion Discussion Discussionsupporting
confidence: 48%
“…There is variability in global practices for the treatment of this disease in the elderly, and social, physiological and pathological characteristics of the elderly population also differ greatly between regions. In Brazil, there are few studies on the subject [19][20][21] . When one considers the population we studied (patients from SUS -National Health System) and procedures performed in the public system teaching hospitals, researches are even scarcer.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The prevalence of complications was low (11.3%), following world's statistics 5,[23][24][25] . Only one death was observed (0.29%), representing a low mortality rate, similar to other studies 10,24,26,27 . The severity of the complications was assessed using CDC 28 Another factor that may play a role in the appearance of complications is surgical duration 19 .…”
Section: Discussionsupporting
confidence: 90%
“…Evidence in uncomplicated acute gallbladder disease suggests that early laparoscopic cholecystectomy is safe and reduces the period of hospitalization 18 . Mean surgical time for laparotomic and laparoscopic cholecystectomies are generally similar between the elderly and younger, and the hospital stay time is higher in elderly patients undergoing laparotomy 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Triennium greatest average of hospital stay time occurred in children under four years of age, followed by those with 70 years or more. A longer hospital stay in elderly patients is usually related to more complications, as they require special care in their preparation and postoperative care and multiprofessional care 12 .…”
Section: Discussionmentioning
confidence: 99%